2017
DOI: 10.3390/ijms18030465
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical-Carbon Dioxide Fluid Extract from Chrysanthemum indicum Enhances Anti-Tumor Effect and Reduces Toxicity of Bleomycin in Tumor-Bearing Mice

Abstract: Bleomycin (BLM), a family of anti-tumor drugs, was reported to exhibit severe side effects limiting its usage in clinical treatment. Therefore, finding adjuvants that enhance the anti-tumor effect and reduce the detrimental effect of BLM is a prerequisite. Chrysanthemum indicum, an edible flower, possesses abundant bioactivities; the supercritical-carbon dioxide fluid extract from flowers and buds of C. indicum (CISCFE) have strong anti-inflammatory, anti-oxidant, and lung protective effects. However, the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…Camphor, borneol, phytol and eucalyptol from the edible flower Chrysantemum indicum also showed potential anti-inflammatory action against acute lung injury in mice [27], a clinical disease with excessive inflammatory response and high mortality rates, and against pulmonary inflammation caused by the anti-tumor drug used to treat rats with hepatoma tumor [8].…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Camphor, borneol, phytol and eucalyptol from the edible flower Chrysantemum indicum also showed potential anti-inflammatory action against acute lung injury in mice [27], a clinical disease with excessive inflammatory response and high mortality rates, and against pulmonary inflammation caused by the anti-tumor drug used to treat rats with hepatoma tumor [8].…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…Moreover, the anti-inflammatory properties and chemical composition of SFE extracts of Chrysanthemum indicum have been comprehensively tackled by several authors. In these works, bioactive polyphenols were identified and quantified by HPLC-DAD, whereas terpenes profiling was carried out by GC-MS analysis [8,27,28,68]. A total of 35 compounds were identified by GC-MS, and 5 phenolics (chlorogenic acid, luteolin-7-glucoside, linarin, luteolin and acacetin) were reconfirmed and quantitatively determined by HPLC-UV [68], as illustrated in Figure 5.…”
Section: Phytochemical Profiling Of Natural Antiviral and Anti-inflammatory Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies revealed an increased level of miR-29b in hepatoma 22 (H22) cells in ascites tumor-bearing mice treated with supercritical-carbon dioxide fluid or scutellarin administration. The treatment further decreased ascites and improved survival (12,13).…”
Section: Introductionmentioning
confidence: 90%
“…Yang et al reported adjuvants that enhance the anti-tumor effect and reduce the detrimental effect of Bleomycin (BLM) in mice [ 9 ]. The supercritical-carbon dioxide fluid extract from flowers and buds of Chrysanthemum indicum (CISCFE) exhibits potent anti-inflammatory, anti-oxidant, and lung protective effects.…”
mentioning
confidence: 99%